2018
DOI: 10.1155/2018/2469486
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine for the Treatment of Psychiatric Disorders: A Review of Current Evidence

Abstract: N-acetylcysteine, a sulphur-containing amino acid for the treatment of paracetamol overdose and chronic obstructive pulmonary disease, is a widely available off-the-shelf oral antioxidant supplement in many countries. With the potential to modulate several neurological pathways, including glutamate dysregulation, oxidative stress, and inflammation that can be beneficial to the brain functions, N-acetylcysteine is being explored as an adjunctive therapy for many psychiatric conditions. This narrative review syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 46 publications
1
52
0
1
Order By: Relevance
“…Echevarria and others (Echevarria et al, 2017) published an extensive review of currently available literature dealing with NAC efficacy in the treatment of cocaine addiction, based on which it can be concluded that NAC may be suitable for reducing the relapse rate in the already abstinent subjects. Similar review about using NAC in the treatment of psychiatric disorders has been recently published by other researchers (Ooi et al, 2018). These authors support the use of NAC as an adjunctive treatment to reduce the total and negative symptoms of schizophrenia, as well as a medication helpful in reducing the cocaine and cannabis use.…”
Section: Sulfane Sulfur In Addictionssupporting
confidence: 69%
“…Echevarria and others (Echevarria et al, 2017) published an extensive review of currently available literature dealing with NAC efficacy in the treatment of cocaine addiction, based on which it can be concluded that NAC may be suitable for reducing the relapse rate in the already abstinent subjects. Similar review about using NAC in the treatment of psychiatric disorders has been recently published by other researchers (Ooi et al, 2018). These authors support the use of NAC as an adjunctive treatment to reduce the total and negative symptoms of schizophrenia, as well as a medication helpful in reducing the cocaine and cannabis use.…”
Section: Sulfane Sulfur In Addictionssupporting
confidence: 69%
“…N-Acetylcysteine (NAC), a precursor of L-cysteine and the antioxidant glutathione (GSH), is found in plants, especially the onion [96][97][98]. NAC has been used as an adjuvant therapy in many psychiatric disorders (e.g., Alzheimer´s disease, schizophrenia, autism, addiction, substance abuse, obsessive-compulsive and mood disorders [24,[99][100][101][102][103][104]), with promising results and no relevant side effects after its administration against inflammation [97]. The use of NAC in a chronic unpredictable mild-stress animal model inhibited the levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in the hippocampus and prefrontal cortex and exhibited antidepressant-like effects [71].…”
Section: N-acetylcysteine Decreases Inflammatory Responsementioning
confidence: 99%
“…The NAC molecule scavenges ROS and there has been growing evidence of its role in attenuating psychiatric and neurological disorders and associated pathophysiological processes such as oxidative stress, mitochondrial dysfunction and glutamate and dopamine dysregulation [96,97,141]. In rats, amphetamine produces oxidative stress (by increasing hydroxyl radical formation and MDA) and dopaminergic neurotoxicity, but treatment with NAC protected against amphetamine-induced damage [84].…”
Section: N-acetylcysteine Exerts Antioxidant Activitymentioning
confidence: 99%
“…Abbreviations: Progression of schizophrenia is increasingly associated with the treatment-resistant (TRS) form of the disease. The severity of symptoms is the result of sulfuric stress and is positively correlated with high levels of homocysteine and the failure of transsulfuration process, which metabolizes homocysteine in the l-cysteine pathway [143,268]. l-cysteine deficiency and lack of response from the transsulfuration pathway (low activity of cystathionine β-synthase and cystathionine γ-lyase) become the cause of the recorded low levels of glutathione and glutathione pathway enzymes (i.e., GPx) in the brain and blood of patients with schizophrenia [269].…”
mentioning
confidence: 99%